ASPECTS OF RESOURCE MANAGEMENT IN COMMERCIAL BANKS - Eshonov Muhammad Ayyub Xoshimjon o`g`li; Tolibjonova Dilobar Bohodir qizi (The latest pedagogical and psychological innovations in education, 2025)
This article examines the essence, key directions, and importance of resource management in commercial banks. It analyzes the strategic role of managing bank resources for capital formation, optimal allocation, liquidity and risk management, and profitability.